Persepsi masyarakat terhadap pengelolaan sampah dan kesediaan membayar (willingness to pay) dalam pelayanan pengelolaan sampah di Distrik Manokwari Barat - Grcae Dharmawati Timang; Ihwan Tjoli; Ludia T. Wambrauw (Program Pascasarjana Universitas Papua, 2019)
This study aims to determine community’s perceptions of waste management, determine the value of Willingness to Pay (WTP) and analyze the household characteristics (X), which as the perception of waste management (X1), income (X2), family number (X3) and education level (X4). These factors are expected to affect the amount of the WTP value. The study was conducted in the District of Manokwari Barat approximately two months (May to June 2016). Total of 60 respondents distributed in 6 villages. Most of the respondents said (55%) that the dustman activities done quite well. However, the placement of the container is limited only in the activity center. The majority respondents (61.67%) only use plastic bags for garbage container. The cost of taking out the trash is Rp. 5000 s / d Rp. 20,000, and the weekly cost they spend Rp. 10.000 s / d Rp. 60,000. The majority respondents (80%) stated that the garbage collecting process has done fairly well, the dustman collecting garbage every day with limited fleet and funds. The majority of respondents (56.67%) said the process of garbage removal and transport has done fairly well, well (21.67%), and unfavorable (21.67%). The majority respondents (61.67%) said that the implementation of the landfill were done well, rubbish was dumped without any treatment. This research result that the WTP group of Rp. 50,000 / month was 60%, the Group of WTP Rp. 75,000 / month was 6.67%, and Group WTP Rp. 100,000 / month was 33.33%. Potential retribution Rp. 1.258.563.333 / month. Based on the multiple regression analysis that the entire household characteristics significantly affect the value of WTP, which the value of R2 was 0,513. The coefficient value of each variables to the WTP were X1 (-14,046.268), X2 (0.005), X3 (-6,882.381), and X4 (9,813.867). The F-test was resulted that Fcount at 14.478 higher than Ftable at 2.54, this mean that all variables simultaneously throughout the study variables significantly influence the public decision give WTP values (Y). Similar results were on the t-test results, partially any study variables significantly influence the decision of the community provides WTP values (Y). The tcount was X1 (-2.897), X2 (2.605), X3 (-2.260), and X4 (2.646) higher than ttable at 1.673.